Edukasi Interaktif dan Aplikasi Media Komik Strip Vaksin COVID-19 Kepada Mahasiswa Sebagai Upaya Pemenuhan Cakupan Vaksinasi COVID-19 Tahap 3 - Anindi Lupita Nasyanka; Janatun Na'imah; Diah Ratnasari (Jurnal Surya Masyarakat, 2021)
Covid-19 is still a health problem for the past two years. Various prevention strategies have begun to be implemented in Indonesia in fighting the COVID-19 pandemic, namely from Work From Home (WFH), 3M's motto, and vaccination. Immunization coverage in Indonesia is still relatively small, which is below 50% until the second stage of vaccination. Therefore, an effort is needed to increase the coverage of COVID-19 vaccination in the third stage, which is targeting students. Students are the millennial generation who like creativity and get bored easily in learning something. This service activity aims to increase student knowledge about Covid-19 vaccination so as to increase vaccination coverage. The method used in this activity werw interactive education for 59 students from two different universities through zoom and distributing comic strip media related to three materials, including an introduction to the immune system, the covid-19 vaccine in Indonesia, and facts and hoaxes about the Covid-19 vaccine. The increase in knowledge was measured using a googleform questionnaire in the form of post-test and pre-test. The results of the activity was showed an increase in knowledge up to 70.82%. In addition, participants who have not vaccinated were willing to immunize after this activity with a percentage of 80%. The distribution of comic strip media was expected to help students remember the information and transmit it to the surrounding community groups.